Wideband Designs of E-shape Microstrip Antenna on Thinner Substrate - Venkata A. P. Chavali; Amit A. Deshmukh (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract Wider bandwidth microstrip antenna employing resonant slot require substrate thickness in excess of 0.07λg, which increases the antenna volume. In this paper, a novel technique to increase the bandwidth in E-shape microstrip antenna fabricated on a thinner microwave substrate, while employing printed resonator elements is proposed. The printed resonator positioned below the patch, introduces TM20 mode nearer to the TM10 mode in E-shape antenna that increases the bandwidth. On substrate thickness of 0.037λg, optimum design achieves bandwidth of 130 MHz (13.89%), with a broadside radiation pattern and peak gain of 7.8 dBi. With the obtained antenna characteristics, proposed thinner substrate designs will find applications in GSM band.